Pengaruh Keterlibatan Pemakai, Kemampuan Teknik Personal dan Ukuran Organisasi Terhadap Kinerja Sistem Informasi Akuntansi pada Hotel Bintang 4 di Kota Denpasar - Reza Firmansyah; Sri Eka Jayanti; I Gst. B. Ngr. P. Putra (Jurnal Riset Akuntansi Warmadewa, 2022)
The reason for this investigation was to analyze how the impact of User Involvement, Personal Technical Ability and Organizational Size on Accounting Information System Performance at 4 Star Hotels in Denpasar City. The example utilized in this examination was 50 respondents. The information was prepared utilizing various direct relapse. Then, at that point the consequences of the exploration show that User Involvement, Personal Technical Ability and Organizational Size affect Accounting Information System Performance. The greatness of the impact of client inclusion, individual specialized capacity and hierarchical size significantly affect the presentation of bookkeeping data frameworks is 61.7%. Ideas that can be given by specialists are 4-star lodgings in Denpasar City in working on the exhibition of bookkeeping data frameworks, which are relied upon to focus on client inclusion, individual specialized abilities and authoritative size.